Efektivitas Edukasi tentang Keunggulan ASI dan Risiko Susu Formula terhadap Pemberian Nutrisi pada Bayi - Indah Hayanti Giawa; Katherine Julia Aruan; Hesti putri Sanulo Duha; Ipemawar Halawa; Tiarnida Nababan (Universitas Pahlawan Tuanku Tambusai, 2026)
Exclusive breastfeeding provides essential nutrition for infants throughout the first six months of life. However, exclusive breastfeeding coverage remains below the expected target due to mothers' limited knowledge of the benefits of breast milk and the risks associated with formula feeding. The purpose of this study was to assess the effectiveness of education regarding the benefits of exclusive breastfeeding and the risks of infant formula in improving infant feeding practices at Pratama Pera Clinic. This quantitative study used a pre-experimental one-group pretest–posttest design involving 30 mothers with infants aged 0–6 months. Questionnaires were administered to participants before and after the educational intervention, and the data were analyzed using univariate analysis and the Wilcoxon Signed Rank Test. The findings indicated that before the intervention, some mothers had low knowledge (3.3%), moderate knowledge (40%), and negative attitudes toward exclusive breastfeeding (63.3%). After the intervention, all respondents (100%) demonstrated high knowledge and positive attitudes. The results of the Wilcoxon Signed Rank Test showed a p-value of 0.001 (p < 0.05), indicating a statistically significant difference between the pretest and posttest results. Therefore, education regarding the benefits of exclusive breastfeeding and the risks of infant formula was effective in increasing mothers' knowledge and attitudes, thereby supporting appropriate infant feeding practices